2020
DOI: 10.1021/acsphotonics.0c01330
|View full text |Cite
|
Sign up to set email alerts
|

On-Chip Transferrable Microdisk Lasers

Abstract: Si photonics has been receiving substantial attention as an integration platform in photonics and optoelectronic research, owing to the ability to manufacture low-cost, compact integrated circuits. However, realizing efficient and high-quality light sources remains a major challenge. Herein, we report an on-chip transferrable low-threshold single microdisk laser, which is fabricated by the microtransfer printing using a structured polymer. The optically transparent and adhesive microtip enables readily reprodu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 31 publications
1
17
0
Order By: Relevance
“…Here, to make the contact surface as wide as possible between the silicon and InGaAsP patch (or to provide a sufficient van der Waals force between them), we introduced a small square post structure with dimensions of 1.5 × 1.5 μm 2 at the center of the silicon ring (Figure 3c), which was far from the resonance mode of the silicon microring resonator (see Supporting Information). The strong mechanical stability of this structure has been verified in recent studies, 37,38 and it can be further improved by filling the remaining spaces with low index materials such as silica 15,16 (see Supporting Information). Finally, by slowly lifting the PDMS stamp, the fabrication of the hybrid micropatch laser was completed, as shown in Figure 3e.…”
Section: ■ Fabricationsmentioning
confidence: 63%
See 1 more Smart Citation
“…Here, to make the contact surface as wide as possible between the silicon and InGaAsP patch (or to provide a sufficient van der Waals force between them), we introduced a small square post structure with dimensions of 1.5 × 1.5 μm 2 at the center of the silicon ring (Figure 3c), which was far from the resonance mode of the silicon microring resonator (see Supporting Information). The strong mechanical stability of this structure has been verified in recent studies, 37,38 and it can be further improved by filling the remaining spaces with low index materials such as silica 15,16 (see Supporting Information). Finally, by slowly lifting the PDMS stamp, the fabrication of the hybrid micropatch laser was completed, as shown in Figure 3e.…”
Section: ■ Fabricationsmentioning
confidence: 63%
“…We theoretically found that the combined hybrid structure with a 2.5 μm radius silicon microring resonator and a 180 nm thick arbitrary-shaped InGaAsP patch produced a high- Q (>10 5 ) resonance mode similar to that of the original silicon microring resonator without the patch. We fabricated the hybrid micropatch lasers with various shapes of InGaAsP patches using transfer printing techniques and experimentally observed that all the structures were operated as lasers with high alignment tolerances.…”
mentioning
confidence: 99%
“…Eventhough, claims for lasing in distributed feedback structures appeared [69], the use of Si-NC as an active laser medium seems improbable. Therefore, alternative approaches are now dominating the research and development of a silicon photonic laser, where either quantum dots and other materials are cointegrated in the silicon chip [70][71][72][73], or hereogeneous integration and chip bonding of III-V semiconductors are used to make a hybrid III-V laser on silicon [74,75,75,76], or, finally, nonlinear effects are exploited [77].…”
Section: Optical Gainmentioning
confidence: 99%
“…However, the key requirement of PICs is the precise integration of the single NW light sources into the pre-existing passive optical components (e.g., optical waveguides (WG) and modulators). This requirement inevitably necessitates individually addressable/manipulable on-demand registration with nanoscale alignment accuracy, which limits the previous efforts to be utilized. Second, it has been considerably difficult to develop a readily applicable and stable scheme for electrical pumping that does not result in significant optical loss.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, we fabricated an all-graphene-contact device by introducing mechanically flexible and optically transparent graphene contacts at the top and bottom surfaces of a semiconductor NW. The vertically p–i–n-doped top-down-fabricated NWs are precisely align-transferred on a target site in a chip by using a microstructured polymer-assisted transfer-printing technique. Electroluminescence (EL) spectroscopy was carried out to demonstrate the successful operation of the device and characterize its optical properties. We also coupled an electrically pumped NW source to a strip-type photonic waveguide (SPWG) to demonstrate the on-demand integration and successfully showed light coupling and waveguiding.…”
Section: Introductionmentioning
confidence: 99%